The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1115/1.3148469
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Expansion by Palmarly Directed Forces to the Transverse Carpal Ligament

Abstract: This study investigated the expansion of the carpal tunnel resulting from the application of palmarly directed forces to the transverse carpal ligament (TCL) from inside the carpal tunnel. Ten fresh-frozen cadaveric hands were dissected to evacuate the carpal tunnel and thus to expose the TCL. A custom lever device was built to apply forces, ranging from 10 to 200 N, to the TCL. Without force application, the carpal tunnel area was 148.4 ± 36.8 mm2. The force application caused the TCL to form arches with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 17 publications
4
60
4
Order By: Relevance
“…These structural changes are likely related to the soft tissue components of the carpal tunnel boundary which provides the carpal tunnel with some degree of compliance [8, 1215]. Recent studies support that the cross-sectional area of the carpal tunnel can be increased by narrowing the carpal arch width (CAW), i.e., distance between the trapezium and hook of hamate [13, 14, 16, 17]. Geometric modeling [16] and in vitro [13, 16] studies have shown that CAW narrowing is associated with palmar bowing of the TCL which increases the height and cross-sectional area of the carpal arch.…”
Section: Introductionmentioning
confidence: 99%
“…These structural changes are likely related to the soft tissue components of the carpal tunnel boundary which provides the carpal tunnel with some degree of compliance [8, 1215]. Recent studies support that the cross-sectional area of the carpal tunnel can be increased by narrowing the carpal arch width (CAW), i.e., distance between the trapezium and hook of hamate [13, 14, 16, 17]. Geometric modeling [16] and in vitro [13, 16] studies have shown that CAW narrowing is associated with palmar bowing of the TCL which increases the height and cross-sectional area of the carpal arch.…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings of the current study indicate that the increase in TCL arch height with increased wrist flexion and finger loading was likely the result of a volarly directed force by the tendons to the TCL. The TCL arching mechanism by flexor tendons is also supported by a previous study demonstrating that the TCL arch height increases when a volarly directed force is applied to the TCL from within the carpal tunnel [23]. …”
Section: Discussionmentioning
confidence: 54%
“…This has all along been challenging to researchers investigating the biomechanical properties and role of the TCL from a computational (Guo et al, 2009;Li et al, 2009;Main et al, 2012) and experimental (Garcia-Elias et al, 1989;Tengrootenhuysen et al, 2009;Xiu et al, 2010) perspective. This paper describes the first approach taken towards determining tensile properties of the TCL using a commercial Maillon Rapide Delta.…”
Section: Discussionmentioning
confidence: 98%
“…This model used a custom lever device to apply known forces that generated TCL arches. In the study by Li et al (2009), a geometric model was also developed to clarify the relationships between the TCL width, CA width, CA height and CA area. The author's model is different but provides a useful approach designed to determine the tensile properties of the intact TCL.…”
Section: Discussionmentioning
confidence: 99%